MENINGKATKAN PERILAKU DISIPLIN BELAJAR SISWA DI ERA PANDEMI MELALUI KONSELING BEHAVIORISTIK DENGAN TEKNIK SELF MANAGEMENT - Atik Mustiati; Indah Lestari; Agung Slamet Kusmanto (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
The aims of this study are: 1. To describe the causes of students' lack of discipline in learning behavior in the pandemic era. 2. Obtaining an increase in student learning discipline behavior in the pandemic era after providing behavioristic counseling services with self-management techniques.This type of research is a qualitative approach and includes case study research. The subjects studied were students of SMK NU Ma'arif Kudus for the academic year 2021/2022, as many as 2 students who had problems with low learning discipline. The method in this research is the method of observation, interviews and documentation.The results of this study indicate the factors causing the undisciplined learning of RF and NN counselees for 3 meetings, namely from internal factors who are both lazy to study and do assignments, play more often with friends and cannot manage time. External factors are both lack of attention from parents and the influence of the surrounding environment.techniques self management can improve learning discipline behavior.